2009
DOI: 10.1177/1367006908353235
|View full text |Cite
|
Sign up to set email alerts
|

The language of anger in Chinese and English narratives

Abstract: This article analyses the language of anger used by the bilinguals in Hong Kong, and examines how the functions of L1 and L2 and users\u27 language proficiency may affect emotional expression. Thirty-three university students in Hong Kong participated in the research. Each was asked to write two stories about \u27an experience in which you were made angry\u27 and \u27an experience in which you made someone angry\u27, one in Chinese and the other in English. A total of 66 narrative texts were collected. The sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, the materials included in ChiE in this paper are all generally regarded a high level of China English. Previous studies (e.g., Dewaele & Pavlenko, 2002;Woon, 2009;Dewaele & Qaddourah, 2016, etc. ) have suggested that language competence influences the emotional expressions of bilinguals.…”
Section: Prepositional Collocates Of Anger Adjectives In the English Varietiesmentioning
confidence: 93%
“…However, the materials included in ChiE in this paper are all generally regarded a high level of China English. Previous studies (e.g., Dewaele & Pavlenko, 2002;Woon, 2009;Dewaele & Qaddourah, 2016, etc. ) have suggested that language competence influences the emotional expressions of bilinguals.…”
Section: Prepositional Collocates Of Anger Adjectives In the English Varietiesmentioning
confidence: 93%
“…AM recall involves two components: the knowledge related to the memory of the event and the activation of the emotional state experienced during the event (Mills & D'Mello, 2014). The prompts for the AMs were created in accordance with previous studies that also used a similar emotion elicitation method to examine the bilingual emotional vocabulary (e.g., Ho, 2009;Marian & Kaushanskaya, 2008). All the participants were asked to write AMs of anger and surprise based on the following prompt: "Write about a real personal experience in which you felt particularly angry/surprised in Spanish/German.…”
Section: Autobiographical Memoriesmentioning
confidence: 99%
“…Chinese lexicon usage is more complex for writing and emotional expression. As a tonal language, a Chinese word may be composed of single or multiple characters (Wierzbicka, 1999;Woon Yee Ho, 2009). Liu and Zhao (2013) imply that emotion expressed in Chinese is more ambiguous than in English since Chinese has more modesty and prudence in positive words.…”
Section: Introductionmentioning
confidence: 99%